THEORETICAL AND METHODOLOGICAL APPROACHES TO THE ANALYSIS OF EXPENSES, INCOME AND FINANCIAL RESULTS BASED ON STATE ENTERPRISE «KHARKIV MECHANICAL FACTORY» REPORTING - Шубіна, Світлана; Малахов, Валерій; Медведєва, Аліна (Socio-economic relations in the digital society, 2019)
The necessity and expediency of further research both theoretical and methodical approaches concerning the analysis of expenses, revenues and fi nancial results of the enterprises activity are substantiated. Themain approaches to the defi nition of the concepts «income», «expenses» and «financial results» are analyzed and the generalized variants of their interpretation on the basis of the investigated scientifi c literature are off ered. Some factors that determine the fluctuations in the volume of income and expenses at enterprises, as well as the processes of their interaction and infl uence on the process of forming financial results are considered. The dynamics of incomes, expenses and financial results on the basis of financial statements of a domestic enterprise — the state enterprise «Kharkiv mechanical factory» — which analysis showed the main obstacles to the formation of profi ts (losses) in relation to the income and expenditure ratio. A phased comprehensive analysis of fi nancial results is proposed taking into account the main factors influencing the chain of «income — expenditure — financial results» and consists of the following main stages: the study of the dynamics of income, expenses and fi nancial results; conducting of factor analysis of gross profit by the determined factors; research of the factor model of net profit; analysis of indicators of profi tability (profitability) of the enterprise by type; generalization of the results of analysis and determinationof reserves for increasing the profi t and profi tability of the enterprise. The ways and suggestions for increasing the efficiency of the research enterprise on the basis of the revealed reserves are proposed. Given the identifi ed key groups of factors, the change in which the most signifi cant impact on the financial performance of the enterprise is the most significant, for the more thorough analysis of the chain «revenues — expenses — fi nancial results» it is proposed to use factor models of gross and net profi ts to control and evaluate the processes of their formation and use.
Keywords: income; expenses; financialresults; grossprofit; net profit; profitability; complex analysis; factor model